Documented territorial specification of publicly funded oral-health benefits in Spain: Delivery models and care pathways - Manuel Jesús Enciso-Ripoll; José Enrique Iranzo-Cortés; Silvia Granero-Ortells; Manuel Bravo; Francisco J. Silvestre (Community Dental Health, 2026)
To compare how official sources specify public oral-health delivery arrangements, territorial extensions, care pathways and reporting across Spain, without inferring actual delivery or access. Comparative documentary analysis of the 17 autonomous communities and the two INGESA-managed cities. Delivery architecture was separated from seven documentary domains. Codes denoted explicit inclusion (E), restricted provision (R), explicit exclusion (X), not identified (N) or insufficiently verifiable evidence (U), relative to the national common baseline. The final evidence set comprised 43 official records: three national and 40 territorial. Twelve territories documented mixed, selective or contracted routes and seven predominantly direct public arrangements. Age-based extensions were explicit in 10 territories and restricted in one. Endodontic provision beyond the national trauma exception was explicit in five and restricted in eight; advanced restorative endpoints were restricted in 11. Orthodontics was restricted in six and explicitly excluded in six; prosthetic provision was restricted in seven and excluded in five. Disability/special-care pathways were explicit in 17 territories. Cervicofacial oncology pathways were explicit in four and restricted in three. Official documents show heterogeneous territorial specification of a common national entitlement, but do not establish utilisation, effective access, quality or outcomes. Delivery architecture was not a proxy for documented clinical scope.